Membrane expression of decay-accelerating factor on neutrophils from normal individuals and patients with paroxysmal nocturnal hemoglobinuria - Okuda, K; Kanamaru, A; Ueda, E; Kitani, T; Nagai, K (Blood, 1990)
Decay-accelerating factor (DAF), a complement-regulating glycoprotein, was found to be a maturational protein for normal neutrophils, and a remarkable correlation was found between the DAF level and alkaline phosphatase activity in neutrophils. We studied the relationship between the amount of DAF on the membrane and cell maturity in total nucleated bone marrow (BM) cells, mature BM and peripheral blood (PB) neutrophils from normal subjects, and patients with paroxysmal nocturnal hemoglobinuria (PNH) using a fluorescence-activated cell sorter with anti-DAF monoclonal antibodies. Percentage distributions of differentiating neutrophils from normal total nucleated BM cells showed that the proportion of immature cells (myeloblasts plus promyelocytes) decreased, while that of mature ones (bands plus segmented forms) increased as the fluorescence intensity increased. For PB neutrophils, no apparent correlation was found between DAF expression and cell maturity. This may have resulted from margination of the fully matured neutrophils with a high amount of DAF. In PNH patients who have low levels of DAF, this study showed that DAF expression in their neutrophils differs from that in normal subjects, and abnormalities occur in PNH cells from a very early stem-cell stage.